2014
DOI: 10.1371/journal.pone.0097108
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Survival in Patients with High-Grade Meningioma and Recurrence-Risk Stratification for Application of Radiotherapy

Abstract: BackgroundRadiotherapy for high-grade meningioma (HGM) is one of the essential treatment options for disease control. However, appropriate irradiation timing remains under debate. The object of this study is to discern which prognostic factors impact recurrence in HGM patients and to propose a risk-stratification system for the application of postoperative radiotherapy.MethodsWe retrospectively reviewed 55 adult patients who were diagnosed with Grade II and III intracranial meningioma. Cox regression models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Considering the results of similar studies, a change in a patient’s mean age at the time of surgery could be observed over the last decades. While the average age a few decades ago was just over 50 years [ 20 , 22 ], meningioma patients who undergo surgery today are approximately 60 years old, similar to this study [ 9 , 21 , 23 , 24 ]. This is not surprising, since the ongoing advances in medicine mean that people are living longer and, consequently, also in the case of patients undergoing surgery.…”
Section: Resultssupporting
confidence: 77%
“…Considering the results of similar studies, a change in a patient’s mean age at the time of surgery could be observed over the last decades. While the average age a few decades ago was just over 50 years [ 20 , 22 ], meningioma patients who undergo surgery today are approximately 60 years old, similar to this study [ 9 , 21 , 23 , 24 ]. This is not surprising, since the ongoing advances in medicine mean that people are living longer and, consequently, also in the case of patients undergoing surgery.…”
Section: Resultssupporting
confidence: 77%
“…While MIB-1 has been correlated with outcomes in some studies, 3,4,31,34,36,[40][41][42]44,45,52,55 this correlation has not been seen in other studies. 1,21,28,48,51 Various cutoff values for MIB-1 in predicting disease grade and progression have been suggested, including 15%, 55 4.2%, 45 3%, 3,31,42,44 2.6%, 52 and 2%. 41 Our results suggest that a value of 3% shows 82.5% specificity in predicting disease progression but only 36% sensitivity.…”
Section: Practical Mib-1 Threshold For Clinical Usementioning
confidence: 87%
“…Here we revealed that genotype was associated with recurrence independently from the degree of surgical resection completeness (Simpson grade) and histological malignancy (Ki-67 LI and WHO grade), which is known as prognostic factors in meningioma. [32][33][34] TRAKLS type was the most favorable genotype, so in addition to evaluating NF2 status, identifying this genotype from non-NF2 meningioma may help the accurate assessment of the recurrent risk. More recently, TERT promoter and PIK3CA mutations were reported to be associated with highly aggressive behavior or tumorigenesis in meningioma.…”
Section: Discussionmentioning
confidence: 99%